Self-medication against COVID-19 in health workers in Conakry, Guinea - Abdoulaye Toure; Saidouba C. Camara; Alioune Camara; Mamoudou Conde; Alexandre Delamou; Ibrahima Camara; Salifou T. Bangoura; Alimou Camara; Mamadou B. Diallo; Mamadou B. Keita; Kaba Kourouma; Robert Camara; et al. (AOSIS, 2022)
Data regarding the prevalence and consequences of self-medication during the COVID-19 pandemic in Africa are very limited. The study aimed to explore the frequency and risk factors of self-medication against COVID-19 by health personnel in this study. This cross-sectional study took place in June 2021, in Conakry, in the all three national hospitals and the six community medical centers, and five primary health centers. A multivariate logistic regression model was performed to identify factors associated with self-medication. A total of 975 health workers with a median age of 31 (IQR: 27-40) years, with 504 (51.7%) women were included. The majority were clinicians: physicians (33.1%) or nurses (33.1%). Of all, 46.2% reported having had at least one COVID-19 symptom during the 12 months preceding the survey. The proportion of self-medication was 15.3% among national hospital staff, 12.20% in municipality medical centers and 22.6% in primary health centers (p=0.06). More than two-thirds (68.7%) who selfmedicated did not have a test for SARSCoV- 2 infection. They took antibiotics including azithromycin, amoxicillin, ampicillin (42.2%), acetaminophen (37.4%), vitamin C (27.9%), hydroxychloroquine (23.8%) and medicinal plants (13.6%). The median duration of self-medication was 4 days. Fatigue or asthenia, sore throat, loss of smell and sore throat of a close person were independently associated with selfmedication. Health care workers largely practiced self-medication during the Covid pandemic and without diagnostic testing. The results suggest the need for training and sensitization of medical personnel to avoid the consequences of the molecules used, including hepatotoxicity and antibiotic resistance.